PENGEMBANGAN PASAR SARUNG TENUN CURA’ LABBA DI DESA TAENG KABUPATEN GOWA - Benget Hutagaol; Andi Irwan Kasim; Muhammad Nogi; Rino Adrian; Budi Prayoga; Nurhannah; Nur Azizah (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2022)
Sarong tenun is one of the cultural heritages that is rich in historical and aesthetic values. Cura' Labba is a typical Makassar woven sarong produced in Taeng Village, Gowa Regency. As the only weavers of the Makassarese sarong Cura' Labba” in the area, they have an important role in strengthening local cultural identity and making a real contribution to the economic growth of the local community. Over time, however, woven sarongs have undergone various developments, both in terms of manufacturing techniques and motif designs. The Cura' Labba woven sarong business still uses traditional looms, namely non-machine looms (ATBM) so that it will be less competitive with similar businesses that use machine technology when viewed from the ability of the amount of production. Due to the covid-19 outbreak, resulting in decreased production and sales, based on this we want to provide education in terms of marketing its products. Marketing of cura 'labba woven sarong must be developed because it is one of the cultural treasures that should be preserved and enhanced. This PKM took place for 2 days, namely October 17-18, 2021 in Taeng Village, Gowa Regency.